Practical application of traditional and cluster set configurations within a resistance training program - Nagatani, T.; Haff, G. G.; Guppy, S. N.; Kendall, K. L. (Strength and Conditioning Journal, 2023)
Altering set configurations during a resistance training program can provide a novel training variation that can be used to modify the external and internal training loads that induce specific training outcomes. To design training programs that better target the defined goal(s) of a specific training phase, strength and conditioning professionals need to better understand how different set configurations affect the training adaptations that result from resistance training. Traditional and cluster set structures are commonly implemented by strength and conditioning professionals as part of an athlete's resistance training program. The purpose of this review is to offer examples of the practical implementation of traditional and cluster sets that can be integrated into a periodized resistance training program.